Analysis of Innovation Diffusion in Environmental Awareness Campaigns Through Educational Content on Instagram EcoBali Recycle - Syahdilla, Mochammad Iqbal; Halakrispen, Sunnaholomi (CV. Publikasi Indonesia, 2025)
People who are not yet aware of the importance of protecting the environment need to be educated and socialized about the importance of being environmentally aware. Education can be done in many ways. EcoBali Recycling brings environmental issues by actively inviting people to minimize waste. The social media they manage displays a lot of education about living with care for waste. This study aims to identify how the EcoBali Recycling community can change people's behavior and mindset in the environmental awareness campaign program on Instagram social media. The method used in this study is a descriptive qualitative method with specifications for tracing information in detail. Specific research requires a systematic flow to obtain the overall analysis of innovation diffusion. The study results show that the Instagram @ecoBaliRecycle has successfully influenced a person's attitudes, opinions, and behavior through persuasive communication, starting from informing, explaining, and convincing people about being environmentally aware. It can be concluded that overcoming waste by changing mindsets and behavior is very important to minimize household waste, manage waste, and sort waste for recycling.